Doing good qualitative research - Cyr, Jennifer 1978- HerausgeberIn; Goodman, Sara Wallace 1979- HerausgeberIn (Oxford University Press, 2024)
In Doing Good Qualitative Research, Jennifer Cyr and Sara Wallace Goodman bring together over forty experts to provide one of the first comprehensive introductions to using qualitative methods across the social sciences. From concept formation and case selection to fieldwork, analysis, write-up, and publication, this volume provides accessible and practical advice to completing a qualitative research project. In addition to the basics of practicing qualitative research, chapters also discuss rarely covered but important topics, including fieldwork and mental health, interviewing vulnerable populations, fieldwork in violent contexts, and conducting fieldwork as a minoritized scholar. Each chapter introduces the theoretical considerations and best practices involved in the application of qualitative data collection and analysis. Additionally, contributors provide first-person accounts of methodology in action, address the expected and unexpected challenges associated with conducting qualitative research, and demonstrate the real-world applications of academic debates. Doing Good Qualitative Research is an engaging one-stop primer for both scholars and students carrying out qualitative research-based projects, from start to finish.